A policy for the disposal of autologous hematopoietic progenitor cells: report from an Italian consensus panel. Issue 9 (24th March 2014) - Perseghin, Paolo; Marchetti, Monia; Pierelli, Luca; Olivieri, Attilio; Introna, Martino; Lombardini, Letizia; Accorsi, Patrizia; Petrini, Carlo; Risso, Marco; Bosi, Alberto; Società Italiana di Emaferesi e Manipolazione Cellulare (SIDEM), Gruppo Italiano Trapianto Midollo Osseo (GITMO) and Centro Nazionale Trapianti (CNT)
<x xml:space="preserve">Abstract</x> Background Autologous stem cell transplantation (ASCT) requires collection and cryopreservation of hematopoietic progenitor cells (HPCs), which in turn may be partially or never reinfused. Thus, HPC storage has become a logistic, ethical, and economic issue. SIDEM, GITMO, and CNT/ISS endorsed a project aimed to define national criteria for HPC disposal aimed to guarantee appropriateness and equity. Study Design and Methods A multidisciplinary panel was convened including HPC harvest and manipulation experts from apheresis units, hematologists with clinical expertise in ASCT, a representative of the national health authority, and a bioethicist. An analytic hierarchy process (AHP) was carried out to select disposal criteria. Results The AHP selected two criteria for prompt disposal of freshly collected HPCs: an abnormal freezing procedure causing highly reduced viability or major microbiology contamination. Moreover, AHP selected six major criteria, each one of them allowing for the disposal of stored HPC units: patient death, withdrawal of consent to ASCT, contraindications or loss of indications to ASCT, a damaged label that prevents correct identification of the unit, and time elapsed since harvest longer than 10 years. Three minor criteria were additionally identified that allowed to anticipate disposal only provided that viability levels are below the limit of acceptance: a documented cold chain interruption, loss of bag integrity, and total amount of stored CD34+ cells lower than 1 × 106/kg or lower than 2 × 106/kg in patients with a successfully completed stem cell transplantation program. Conclusions A formal consensus process allowed SIDEM and GITMO to propose a policy for autologous HPC disposal that fulfills clinical, ethical, and economic criteria.